2007
DOI: 10.1300/j463v03n02_02
|View full text |Cite
|
Sign up to set email alerts
|

Intimate Partner Violence and HIV Sexual Risk Behavior Among Latino Gay and Bisexual Men

Abstract: This study examined the relationship between intimate partner violence (IPV) and HIV sexual risk behavior using a probability sample of 912 Latino gay and bisexual men from three U.S. cities. Prevalence estimates of psychological, physical, and sexual abuse are higher in our sample than usually found in the general population of gay and bisexual or heterosexual men, with 52% reporting some type of abuse. IPV also was associated with being HIV positive. Controlling for HIV status, age, and immigrant status, all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
41
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 28 publications
4
41
0
Order By: Relevance
“…Intimate partner violence was measured using a modified version of the Conflict Tactics Scale (Feldman, et al, 2008), which includes three yes/no questions regarding victimization and three yes/no questions regarding perpetration: Have you ever been insulted or verbally abused by a lover or boyfriend?Have you ever been hit, kicked, or slapped by a lover or boyfriend?Have you ever been sexually abused or raped by a lover or boyfriend?Have you ever insulted or verbally abused a lover or boyfriend?Have you ever hit, kicked, or slapped a lover or boyfriend?Have you ever sexually abused or raped a lover or boyfriend? …”
Section: Methodsmentioning
confidence: 99%
“…Intimate partner violence was measured using a modified version of the Conflict Tactics Scale (Feldman, et al, 2008), which includes three yes/no questions regarding victimization and three yes/no questions regarding perpetration: Have you ever been insulted or verbally abused by a lover or boyfriend?Have you ever been hit, kicked, or slapped by a lover or boyfriend?Have you ever been sexually abused or raped by a lover or boyfriend?Have you ever insulted or verbally abused a lover or boyfriend?Have you ever hit, kicked, or slapped a lover or boyfriend?Have you ever sexually abused or raped a lover or boyfriend? …”
Section: Methodsmentioning
confidence: 99%
“…IPV has been linked to increased risk of HIV acquisition. 19 Those experiencing IPV often cite inequalities and fear of violence as reasons for not negotiating condom use. 19 20 TG individuals also experience numerous difficulties in seeking help from police after violent experiences, 21 thus creating a barrier to leave current abusive partners.…”
Section: Discussionmentioning
confidence: 99%
“…[58] Another study that focused exclusively on gay and bisexual Hispanic men, identified lifetime IPV at 52%; [59] HIVinfected men with higher rates of IPV also had higher rates of high risk sexual behaviors. [12] These same Hispanic gay men have much higher rates of unprotected anal intercourse and binge drinking.…”
Section: Minority Syndemicsmentioning
confidence: 99%